La réglementation de l’industrie québécoise du camionnage : aperçu et considérations analytiques - Boucher, Michel (L'Actualité économique, 1981)
ABSTRACTThis paper examines the role and practices of the Quebec Transport Commission (QTC), and attempts to assess the significance of regulatory restrictions in this province and their impact on the performance of the Quebec trucking industry. So the interpretation given by the QTC to the test of "public convenience and necessity" makes the requirement for a licence a major obstacle to entry. The rate approval process in Quebec, on the other hand, appears to be largely a formality; the proportion of requests for rate changes granted in whole or in part by the QTC tends to generally be well over 90 percent. These aspects, along with the significant role of the Quebec Tariff Bureau, suggest that regulation is likely to substantially reduce competition and provide for the realization of monopoly rents. However, a number of factors have eroded the influence both of the QTC and the Quebec Tariff Bureau. The availability of substitute transport services has substantially reduced the effects of the QTC's entry restrictions. In this regard, it is refered specifically to the services of freight brokers and leasing (or pseudo-leasing) firms, and to the potential alternatives in the form of rail and private carriage. In addition, "illegal trucking" has become an important phenomenon in the province as a result of the rather lax enforcement of the Commission's regulations and the low fines for violations. As for the activities of the Quebec Tariff Bureau, it is pointed out that it does not and could not effectively "cartelize" the industry given its inability to enforce rates and production quotas, and the strong incentive of individual members to undermine any such cartel. An examination of various aspects of the performance of the Quebec trucking industry was found to confirm the importance of competitive factors. Although some permits in the province have acquired a market value, these were estimated to be quite low (as a percentage of operating revenue), well below the levels found for the U.S. This suggests that regulation is not giving rise to very substantial excess profits for the industry as a whole. A comparison of before-tax rates of return for firms in Quebec and firms in Alberta supports this finding. More generally, the analysis of market structure and performance leads to the conclusion that trucking regulation in Quebec is largely ineffective. The availability of intra-modal and inter-modal substitutes has considerably reduced the impact of regulation on industry performance and greatly diminished its negative consequences for allocative efficiency.